Seasonal changes in leg strength and vertical jump ability in internationally competing ski jumpers - Ronnestad, B. R. (European Journal of Applied Physiology, 2013)
The aim of the present study was to investigate the effects of the seasonal changes in heavy strength training on maximal strength and vertical jump ability in internationally competing ski jumpers. A repeated-measures design was used to follow-up the changes in strength, vertical jump capacity, and neuromuscular efficiency (expressed as the ratio between squat jump height and the relative isometric force) in the ski jumpers. Measurements were performed in November (pre), January (middle of the competition season), and in March (end of the competition season). The weekly number of strength training sessions, absolute, and relative peak isometric squat force was significantly reduced during the competition period (p < 0.05). The body mass was reduced from pre-season to the middle of the competition season and remained at this level at the end of the competition season (p < 0.05). Squat jump height remained unchanged from pre-season until the end of the competition season (p < 0.05). Neuromuscular efficiency increased from pre-season until the end of the competition season (p < 0.05). The present study shows that maximal strength and body weight is reduced from pre-season to the end of the competitive season in internationally competing ski jumpers. The vertical jump ability did not change from pre-season to the end of the competitive season, while the neuromuscular efficiency increased during the competitive season. These findings indicate that coaches and athletes should emphasize adequate nutritional strategies and to apply a larger focus on strength maintenance training during the competitive season to maximize ski jump performance.